제주 로컬 드라마의 로컬리티 재현 양상 연구 － <우리들의 블루스>와 <웰컴투 삼달리>를 중심으로 - 최아름; Choi A-reum (인문학연구, 2025)
본 연구는 특정 지역을 배경으로 개성 있는 지역색을 최대한 살려낸 드라마를 ‘로컬 드라마’로 규정하고, 이들 드라마가 극 중에서 지역의 로컬리티를 어떠한 방식으로 재현하고 있는지를 분석하였다. 이를 위해 로컬과 로컬리티를 구성하는 핵심 요소들에 대해 살펴보고, 이 요소들이 드라마 서사에 어떻게 반영되고 구현되는지를 고찰하였다. 특히 제주도를 주요 배경으로 한 작품에 주목하여 제주 로컬 드라마의 재현 양상과 한계를 짚어보면서, 사례 분석 대상인 <우리들의 블루스>와 <웰컴투 삼달리>에 나타난 제주 로컬리티의 재현 양상을 로컬리티의 구성요소와 드라마 속 공간, 인물, 사건 간의 유기적인 결합 측면에서 살펴보고자 하였다. 그중에서도 해녀의 삶을 통해 드러나는 바다에 대한 인식과 섬이라는 지리적 특수성에 기반한 공동체 문화의 재현이라는 두 가지 측면에 초점을 맞춰 분석하였다. 이들 드라마는 해녀문화와 궨당문화를 중심으로 지역 고유의 사회·문화적 맥락을 서사 구조에 통합함으로써, 제주의 로컬리티를 단순한 배경이 아닌 핵심적인 서사적 동력으로 기능하게 하고 있다. 본 연구는 이러한 분석을 바탕으로, 로컬 드라마가 지역의 고유성과 삶의 층위를 편견과 왜곡 없이 재현하기 위해 고려해야 할 재현 방향성을 제시하고, 향후 로컬 드라마의 학술적 개념화의 토대를 마련하고자 한다. This study defines television dramas that vividly incorporate distinctive regional characteristics as “Local Drama” and analyzes how these works represent locality within their narratives. This study examines the core elements that constitute the concepts of the local and locality, and ex’plores how these elements are reflected and realized within the narrative structures of television dramas. Focusing particularly on works set in Jeju Island, it investigates the patterns and limitations of representing Jeju’s locality in local dramas. Through a case analysis of Our Blues and Welcome to Samdal-ri, this paper aims to explore how Jeju’s locality is represented, considering the organic interplay between the components of locality and the drama’s space, characters, and events. Particular attention is given to two key aspects: the representation of the sea as perceived through the lives of haenyeo (Jeju's traditional female divers), and the representation of communal culture shaped by the island’s geographical and sociohistorical conditions. These dramas incorporate haenyeo culture and Gwaendang(a Jeju-specific community network) not merely as background elements but as core narrative drivers that structure character development and dramatic progression. Based on these findings, this study proposes representational directions for local dramas that aim to depict regional identity and lived experience without distortion or bias, thereby contributing to the conceptual foundation for future scholarly conceptualizations of local drama genre.